The Urgency of Pancasila and Citizenship Education to Strengthen National Character with Global Citizenship Dimensions - Mas'ud Roziq Afan; Ardhana Januar Mahardhani; Hadi Cahyono; Zamawi Chaniago (STAI Hubbulwathan Duri, 2024)
Pancasila and Citizenship Education (PPKn) is vital in fostering student character aligned with Pancasila values and promoting global citizenship awareness. This study examines the role of PPKn in addressing educational challenges in globalization and character development. A literature study approach was adopted, analyzing diverse sources, including scientific journals, books, and articles, to gain insights into the implementation of PPKn in education. Findings reveal that PPKn significantly shapes student character through Pancasila principles, such as mutual cooperation, social justice, and respect for diversity. Furthermore, PPKn enhances students' global awareness on issues like human rights, cultural diversity, and social responsibility. As a compulsory subject at all educational levels, PPKn integrates global values into its curriculum to prepare students for challenges like climate change, social inequality, and cultural conflict. By adopting innovative learning methods, PPKn cultivates a generation with integrity, strong character, and the capability to contribute at an international level. The integration of local and global perspectives in PPKn supports the creation of a national identity that is adaptive to modern demands. PPKn plays a pivotal role in character education and global readiness, ensuring students are equipped to address contemporary issues and contribute positively to society. This reinforces the development of a nation's character, responsive to the challenges of globalization.